Ordinances of the Council of the City of Dallas and Annual Reports of City Officers from October 1st, 1886 to June 25th, 1888, at 80, An Ordinance Prohibiting and Punishing the Unlawful Carrying of Arms, § 1 (1888) - (:unkn) unknown (My University, 1887)
Be it ordained by the City Council of the City of Dallas, that if any person in the City of Dallas shall carry on or about his person, saddle, or in his saddle-bags, any pistol, dirk, dagger, slungshot, sword- cane, spear, or knuckles made of any metal or hard substance, bowie knife, or any other kind of knife manufactured or sold for purposes of offense or defense, he shall be punished by fine of not less than twenty-five nor more than two hundred dollars and shall be confined in the city prison not less than twenty nor more than sixty days.
Keywords: CARRY